Economic impact of treating invasive mold disease with isavuconazole compared with liposomal amphotericin B in the UK. (September 2018) - Bagshaw, Emma; Enoch, David A; Blackney, Michael; Posthumus, Jan; Kuessner, Daniel
Aim: Invasive mold diseases (IMDs) are associated with significant morbidity and mortality. Approved treatments include voriconazole (VORI), liposomal amphotericin B (L-AMB), posaconazole (POSA) and isavuconazole (ISAV). A UK-based economic model was developed to explore the cost of treating IMDs with ISAV versus L-AMB followed by POSA.Materials & methods: As indirect comparisons have demonstrated similar efficacy between the comparators, a cost-minimization approach was taken. Drug acquisition, administration & monitoring, and hospitalization costs were evaluated from the healthcare system perspective.Results: Per-patient costs were UK£14, 842 with ISAV versus UK£18, 612 with L-AMB followed by POSA. Savings were driven by drug acquisition, and administration & monitoring costs.Conclusion: ISAV has the potential to reduce IMD treatment costs relative to L-AMB followed by POSA.